Nitric oxide and prostaglandins - Important players in endothelin-1 induced myocardial distensibility - Brás-Silva C (2008)
This study investigated whether endothelin (ET)-1-induced increase in myocardial distensibility is preserved in heart failure (HF) and whether it is modulated by nitric oxide (NO) and prostaglandins. New Zealand white rabbits were treated with doxorubicin (1 mg/kg, intravenously twice a week for 8 weeks, DOX-HF group) or saline (control group). Effects of ET-1 (0.1, 1, 10 nM) were tested in papillary muscles from the DOX-HF group and a control group in the presence of: i) intact endocardial endothelium (EE); ii) damaged EE; iii) N-G-nitro-L-arginine (L-NNA; NO synthase inhibitor), and iv) indomethacin (INDO; cyclooxygenase inhibitor). In the presence of an intact EE, ET-1 promoted concentration-dependent positive inotropic and lusitropic effects that were maintained after damaging the EE, in the presence of L-NNA or INDO and in the DOX-HF Group. ET-1 reduced resting tension at the end of the isometric twitch (increased diastolic distensibility) by 3.2 +/- 1.3 %, 6.0 +/- 1.6 % and 8.8 +/- 2.7 % (at 0.1, 1 and 10 nM, respectively), in muscles with intact EE, effect that was completely abolished after damaging EE, in the presence of L-NNA or INDO or in the DOX-HF Group. This study demonstrated that the increase in myocardial distensibility induced by ET-1 is absent in HF and is dependent of NO and prostaglandin release.